Commission on Audit employees cooperative association of region eight A study on determining how democracy functions in a cooperative. - Tabao, Golda Meir T. (Tacloban City Golda Meir T. Tabao, 2009)
Cooperatives are set in a way that it can help its members through the services it can offer. Basically, cooperatives help the people and make them empowered and in the long run make it possible for them to be independent and stable. With the emergence of cooperatives it is best that such interest be regarded on this kind of organization.
The purpose of this study then is to determine the level of democratization and development in the Commission on Audit Employees Cooperative Association of Region Eight (COACARE). Study connecting democratization and development with cooperatives are hardly ever done. In order to do this the following variables were used: membership, cooperatives as democratic organizations, share capital or members' contribution, provisions made to educate. Furthermore, guide questions were prepared and pertinent papers were gathered to further supplement the study. The result of the study would determine the relationship of democratization and development with cooperatives.
Undergraduate thesis (B.A.S.S. Political Science)--University of the Philippines, Tacloban.
Keywords: Social Science